Responsibility of Local Government in Ensuring the Rights of Informal Sector Workers: A Case Study of Illegal Parking Attendants in Tanah Abang - Rama Nugraha Alvareza; Muhammad Kamal; Askari Razak (Fakultas Hukum, Universitas Muslim Indonesia, 2026)
This study aims to analyze the responsibility of the DKI Jakarta Provincial Government in managing illegal parking attendants in the Tanah Abang area and its conformity with the principles of the rule of law and the fulfillment of the right to work. The study employs an empirical method with descriptive and prescriptive approaches to examine the gap between legal norms and social realities. The findings indicate that the existence of illegal parking attendants is a structural phenomenon influenced by limited access to formal employment and the high demand for parking services in urban areas. The policy approach, which has predominantly been repressive, has not been able to resolve the root causes and instead tends to create a recurring cycle between enforcement and the re-emergence of illegal parking practices. From the perspective of the rule of law, the implementation of Regional Regulation Number 5 of 2012 on Parking has not fully reflected the principles of legality, justice, and expediency. The fulfillment of the right to work requires the local government not only to enforce order but also to provide access to decent employment, legal protection, and social security for informal sector workers. Therefore, policy reform is needed through inclusive, adaptive, and data-driven measures, including data collection, administrative recognition, simplification of licensing, and strengthening of empowerment and job training programs. A comprehensive approach integrating legal, social, and economic aspects is expected to achieve substantive justice and improve public welfare sustainably.